Combination of Docetaxel (Taxotere) and Cisplatin in Patients with Breast Cancer: A New Therapeutic Approach - Uddin, Dayem; Islam, Quazi Tarikul; Begum, Khodeja Nahar (TAJ: Journal of Teachers Association, 2011)
DOI: http://dx.doi.org/10.3329/taj.v15i1.8380 TAJ 2002; 15(1): 35-36